The Effectiveness of Technology-Based Daily Food Recording in Increasing Children's Daily Intake: Literature Review - Nafista, Ulfia Fitriani; Fatkuriyah, Lailil (Jurnal Kesehatan Komunitas Indonesia, 2023)
The technology-based daily recording of children's dietary is expected to be able to provide an easier overview of children's nutritional status. So, it will reduce the number of nutritional imbalances in children. This research aimed to know to determine the effectiveness of children's daily dietary recording with an application to estimate children's nutritional needs. The research method was used a literature review study. Result: From the results of the study, it was concluded that the use of food recording applications, either using photos or not, provides increased information on children's daily nutrition. The application allows an estimation of children's diet's food portions and nutrition. It may become a benchmark for parents or health workers in providing children's diets. The dietary assessment application can be used in the community and hospitals to monitor children's nutrition status. It is recommended that further research include food waste in the calculation so that the daily energy estimate is more accurate.